Shift work relationships with same- and subsequent-day empty calorie food and beverage consumption - Lin, Ting-Ti; Park, Chang; Kapella, Mary C.; Martyn-Nemeth, Pamela; Tussing-Humphreys, Lisa; Rospenda, Kathleen M.; Zenk, Shannon N. (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'Shift work may contribute to unhealthy eating behaviors. However, the evidence is built mainly on comparisons of eating behaviors between shift and non-shift workers. Growing research has suggested daily experiences and exposures may contribute to daily fluctuations in people’s food consumption. The purpose of this study was to examine within-person associations between shift work and same- and subsequent-day empty calorie food/beverage consumption. ' ' METHODS ': 'This was a 14-day intensive longitudinal study using ecological momentary assessment. A convenience sample of 80 hospital registered nurses working a rotating shift in Taiwan completed a 21-item food checklist assessing their empty food/beverage consumption (ie, fast/fried food, sweet and salty snacks, sugar-sweetened beverages) four times at random daily. Daily shift work (ie, day, evening, or night shift) was derived from the registry-based work schedule. Three-level mixed-effects regression models were employed for hypothesis testing. ' ' RESULTS ': 'A total of 77 participants with 2444 momentary assessments were included in the final analysis. The results suggested that participants on night compared to day shifts had higher likelihoods of fast/fried food intake [adjusted odds ratio (ORadj) 1.7, 95% CI 1.2–2.6] and sugar-sweetened beverage consumption (ORadj 1.5, 95% CI 1.0–2.1). However, there were no significant associations between shift work and subsequent-day empty calorie food/beverage consumption. ' ' CONCLUSIONS ': 'Night shift work is associated with same-day increased empty calorie food/beverage consumption among workers. Strategies that help to prevent unhealthy eating behaviors on night shifts may help to reduce rotating shift workers’ empty calorie food/beverage consumption and ultimately improve their health.
Keywords: beverage consumption; calorie; circadian rhythm; eating behavior; ecological momentary assessment; empty calorie; empty calorie food; food consumption; shift work; shift work relationship; shift worker